Novel Analysis on Aroma Compounds of Wine, Vinegar and Derived Products - Castro-Mejías, Remedios; Durán-Guerrero, Enrique (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Aroma compounds are some of the main compounds responsible for the acceptance of oenological products such as wine, vinegar and derived products. These kinds of compounds are produced during the winemaking process and they can be affected by natural, geographical and human factors: raw material, alcoholic and acetic fermentation, ageing, distillation, technological processes, etc. Therefore, it is very important to study and to characterize the aromatic fraction of these oenological beverages in order to improve the quality of the final product. Therefore, this book is focused on some recent studies related to the study of the volatile composition of wine, vinegar and derived products, in many different fields of science: oenology, chemistry, food science and technology, biochemistry, microbiology, biotechnology, engineering, sensory analysis, etc., and it shows the great importance of both sensory and analytical study of oenological products aroma and how they are influenced by the different stages and conditions under which they are elaborated. In this book, you will find 12 valuable scientific contributions: 2 literature reviews and 10 original research works, which deal with the latest advances in both sensory and analytical tools in order to evaluate the effects of different techniques or winemaking stages on the oenological products' aromas.